Photoswitching adsorption selectivity in a diarylethene–azobenzene MOF. Issue 4 (21st December 2016) - Fan, Cong Bin; Liu, Zhi Qiang; Gong, Le Le; Zheng, An Min; Zhang, Le; Yan, Chang Sheng; Wu, Hui Qiong; Feng, Xue Feng; Luo, Feng
Abstract : The first photoactive MOF composed of both azobenzene and diarylethene units is reported and used to modulate adsorption selectivity via light. Abstract : The first MOF (metal–organic framework) built on both diarylethene and azobenzene photochromic units is reported here and displays distinct photoresponses for different guest molecules, thus creating an easy-to-use pathway to modulate the adsorption selectivity of MOF materials.